THE USE OF RAPESEED OIL METHYL AND ETHYL ESTERS AND OF RAPESEED OIL-DIESEL MIXTURES AS FUELS FOR DIESEL ENGINE - Eliçin, Ahmet Konuralp; Öztürk, Ferhat; Baran, Mehmet Fırat; Esgici, Reşat (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2019)
This study was conducted over a year period incorporating one growing seasons of 2013–2014 with the aim being to investigate the effects of the free fatty acid and yield characteristics of different rapeseed genotypes planted at different sowing times in the climate of Diyarbakır, Turkey on biodiesel production, on engine performance and on emission values. The study was conducted in the trial areas of the Department of Field Crops of the Dicle University Faculty of Agriculture, in which the quality traits of the rapeseed (oil ratio and fatty acid content) were analyzed. The genotypes, ‘Licord’ was achieved the highest oil content (38.13%). The highest alpha-linolenic acid (1.25%), and oleic acid (65.1%) were recorded from the genotype ‘Express’. The highest linoleic acid (18.16%) was achieved from Lirown genotype. Among the different varieties of rapeseed, those with the highest oil ratio and fatty acid content were selected and subjected to transesterification to obtain rapeseed oil methyl and ethyl esters. These were then tested in a small power diesel engine in accordance with the EN 14214 standard, which is considered applicable by the Energy Market Regulatory Board of Turkey for the investigation of the performance and emission characteristics of such ester fuels. The study made use of single-cylinder, direct injection, four-cycle, 5.5 kW nominal power diesel engine. The use of fatty acid esters was found to give moment and power values close to those of diesel engine fuel, although the ester fuels showed a slight increase in fuel consumption values. The transesterification of rapeseed was found to reduce viscosity and to decrease calorific value and specific weights. Emission values for CO and CO2 were found to be lower than number 2-D diesel fuel, while an increase was observed in the level of NOx.
Keywords: Emission; Fatty acid compositions; Rapeseed; Performance; Transesterification